Emuna i pistis - Mech, Krzysztof (Przegla̜d religioznawczy, 2013)
The article juxtaposes and analyzes Old Testament's emuna and New Testament's pistis. These concepts express the experience of faith which is present in the Bible and contain rich meaning, which my text is attempting to expose. We will follow the paths of biblical faith experience in order to show their diversity and ambiguity. We will define what semantic areas are being evoked by emuna and pistis, as well as to what extent these areas overlap each other, and to what extent do they differ. In the presented analyses we will refer to such a tradition of reading of biblical texts, which regards that the archetype of the faith relation is the relation of trusting an another person.